Rare purulent pericarditis caused by carbapenem-resistant Acinetobacter baumannii: A case report. Issue 38 (September 2019) - Liu, Jingjing; Xiao, Xuefei; Cen, Chaoqun; Yuan, Hong; Yang, Mingshi
Abstract: Background: Pericardial infection caused by Acinetobacter baumannii is rare, particularly that of carbapenem-resistant A baumannii (CRAB). Case presentation: We describe a rare case of purulent pericarditis due to CRAB in a 76-year-old man with acute myocardial infarction and acute kidney injury. The man was admitted to the intensive care unit for a catheter-related bloodstream infection. Pericardial effusion was detected via the bedside X-ray and ultrasound, and pericardiocentesis was performed. Cultures of the pericardial fluid, catheter tip, and blood independently revealed the presence of CRAB. These findings confirmed a diagnosis of purulent pericarditis. Conclusions: Clinicians should be reminded that CRAB infection can lead to purulent pericarditis, particularly in patients with congestive heart failure or renal insufficiency.